Quasianalytic functionals and projective descriptions - Bonet, José; Meise, Reinhold (MATHEMATICA SCANDINAVICA, 2004)
The topology of the weighted inductive limit of Fréchet spaces of entire functions in $N$ variables which is obtained as the Fourier Laplace transform of the space of quasianalytic functionals on an open convex subset of $R^N$ cannot be described by means of weighted sup-seminorms.